2018
DOI: 10.13189/aeb.2018.060105
|View full text |Cite
|
Sign up to set email alerts
|

Private Investment and the Effects of Decentralisation and Regional Competition between Mexican Cities

Abstract: The increasing mobility of capital raises competition between territories in order to attract it within their jurisdiction. Since 1994, the decentralisation process in Mexico has been accelerated by providing municipalities with greater funds. In parallel, Mexican municipalities have participated more actively on policymaking. Both facts should have allowed municipalities to enhance competitive advantages and increase their attractiveness. In spite of the increasing resources and local participation in policym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, it was demonstrated that, in the short term, European regions tend to behave as competitors for investment fixing, but in the long run innovation has the potential to generate spillover effects on the neighbours of the region, which is consistent with Rodríguez-Pose and Crescenzi (2008). We list this result as strategic behaviour, typical of the phenomenon studied as a "coopetition" (Blonigen & Kolpin, 2007;Ibarra, 2018) by which competing agents gain in the long term due to strategic behaviours.…”
Section: Exploring the Spillover Effects Of Regional Innovation Acros...mentioning
confidence: 53%
“…Therefore, it was demonstrated that, in the short term, European regions tend to behave as competitors for investment fixing, but in the long run innovation has the potential to generate spillover effects on the neighbours of the region, which is consistent with Rodríguez-Pose and Crescenzi (2008). We list this result as strategic behaviour, typical of the phenomenon studied as a "coopetition" (Blonigen & Kolpin, 2007;Ibarra, 2018) by which competing agents gain in the long term due to strategic behaviours.…”
Section: Exploring the Spillover Effects Of Regional Innovation Acros...mentioning
confidence: 53%